FONOLOGI GENERATIF BAHASA TOTOLI (Generative Phonology of Totoli Language) - Gari, Siti Fatinah; Tamrin, NFN; B, M Asri (Kandai, 2023)
This study investigates the realization of segments, syllable patterns, and the characteristics of Totoloi language. Therefore, this study aims to find and describe the realization of segments, syllable patterns, and characteristics of segments of Totoli language thorugh the generative phonology theory which developed by Chomsky and Morris Halle and adapted by Schane (1993). The data was obtained using listening method through tapping, taking notes, listening to conversational engagement techniques. Then, it was analyzed using the intralingual equivalence method with the equating comparison and discriminating comparison techniques. This study found that there were 32 segments of Totoli language, namely 8 vowel segments: /o/, /ɔ/, /u/, /i/, /e/, /ɛ/, /a/, /ɐ/, /a:/, /o:/, dan /i:/; and 24 consonant segments: /p/, /b/, /ɓ/, /m/, /w/, /r/, /t/, /s/, /ɗ/, /n/, /l/, /ɽ/, /Ɉ/, /ɲ/, /j/, /k/, /g/, /ŋ/, /h/, /nɗ/, /mb/, /mp/, /ŋg/, /nt/, /nɈ/, /ɗɗ/, /kk/, /ll, /ss/, and /pp/. Totoli language had a single-margin syllable canonical pattern: V/KV/KVK. By using 14 distinctive features, it was found that all vocal segments had characteristics as follows [+Sil] and [+Son]; /m/, /n/, /ɲ/, /ŋ/, /mb/, /mp/, /nɗ/, /nt/, /nɈ/, /ŋg/, /r/, /ɽ/,/j/, /w/ had characteristics as follows [+Son]; all consonant segments, except /h/, /w/, /j/ had characteristic as follows [+Kon];  /s/, /h/ had characteristics as follows [+Kont]; only /s/ had characteristics as follows [+Strid]; /m/, /n/, /ɲ/, /ŋ/, /mb/, /mp/, /nɗ/, /nt/, /nɈ/, /ŋg/, had characteristic as follows [+Nas]; /l/, /ɽ/ had characteristics as follows [+Lat]; /p/, /b/, /ɓ/, /t/, /ɗ/, /ɗɗ/, /m/, /n/, /mb/, /mp/, /nɗ/, /nt/, /r/, /w/ had characteristics as follows [+Ant]; /t/, /ɗ/, /Ɉ/, /nɗ/, /nt/, /nɈ/, /s/, /l/, /ɽ/ had characteristics as follows [+Kor]; /i/, /i:/ had characteristics as follows [Tin]; /a/, /a:/, /ɐ/ had characteristics as follows [+Ren]; /u/, /o/, /ɔ/, /k/, /g/ had characteristics as follows [+Bel]; and /u/, /o/, /ɔ/ had characteristics [+Bul]. Feature of [+Ppt] was not found in Totoli language.  Penelitian ini menelaah satu rumusan masalah, yaitu bagaimanakah realisasi segmen, pola kanonik suku kata, dan fitur-fitur distingtif segmen bahasa Totoli? Sejalan dengan itu, penelitian ini bertujuan menemukan dan mendeskripsikan realisasi segmen, pola kanonik suku kata, dan fitur-fitur distingtif segmen bahasa Totoli melalui teori fonologi generatif yang dikembangkan oleh Chomsky dan Morris Halle dan diadaptasi oleh Schane (1992). Data diperoleh menggunakan metode simak melalui teknik sadap, catat, simak libat cakap, dan simak bebas libat cakap. Kemudian, dianalisis menggunakan metode padan intralingual dengan teknik hubung banding menyamakan dan hubung banding membedakan. Penelitian ini menemukan 39 segmen bahasa Totoli, yaitu 10 segmen vokoid: /o/, /u/, /i/, /e/, /e:/, /a/, /a:/, /o:/, /u:/, dan /i:/; dan 29 segmen kontoid: /p/, /b/, /ɓ/, /m/, /r/, /t/, /s/, /ɗ/, /n/, /l/, /ɽ/, /Ɉ/, /j/, /k/, /g/, /ŋ/, /nɗ/, /mb/, /mp/, /ŋg/, /nt/, /nɈ/, /ɗɗ/, /kk/, /ll, /tt/, /bb/, /mm/, dan /ss/. Bahasa Totoli memiliki pola kanonik suku kata margin tunggal: V, KV, KVK. Dengan menggunakan 14 fitur distingtif ditemukan bahwa semua segmen vokal bercirikan [+Sil] dan [+Son]; /m/, /mm/, /n/, /ɲ/, /ŋ/, /mb/, /mp/, /nɗ/, /nt/, /nɈ/, /ŋg/, /r/, /ɽ/,/j/, /w/ bercirikan [+Son]; semua segmen konsonan, kecuali /j/ bercirikan [+Kon]; /s/ bercirikan [+Kont]; hanya /s/ dan /ss/ bercirikan [+Strid]; /m/, /mm/, /n/, /ŋ/, /mb/, /mp/, /nɗ/, /nt/, /nɈ/, /ŋg/, bercirikan [+Nas]; /l/, /ɽ/ bercirikan [+Lat]; /p/, /b/, /ɓ/, /bb/, /t/, /ɗ/, /ɗɗ/, /m/, /n/, /mb/, /mp/, /nɗ/, /nt/, /r/ bercirikan [+Ant]; /t/, /ɗ/, /Ɉ/, /nɗ/, /nt/, /nɈ/, /s/, /ss/, /l/, /ɽ/ bercirikan [+Kor]; /i/, /i:/, /k/, /kk/ bercirikan [+Tin]; /a/, /a:/ bercirikan [+Ren]; /u/, /u:/, /o/, /o:/, /k/, /kk/, /g/ bercirikan [+Bel]; dan /u/, /u:/, /o/, /o:/ bercirikan [+Bul]. Fitur [+Ppt] tidak ditemukan dalam bahasa Totoli.